Accessing Care Through the Veterans Choice Program: The Veteran Experience - Sayre, George G. (J Gen Intern Med, 2018)
BACKGROUND: The Veterans Choice Program (VCP) was implemented to improve healthcare access by expanding healthcare options for Veterans Health Administration (VHA) enrollees. OBJECTIVES: To understand Veterans’ experience accessing VCP care. DESIGN: Qualitative content analysis. SUBJECTS: Forty-seven veterans from three medical centers in three of the five VA geographical regions. APPROACH: We used semi-structured telephone interviews designed to elicit descriptions of Veterans’ experiences. Data was analyzed using iterative, inductive, and deductive content analysis. Broad themes were identified based on representative interview responses. KEY RESULTS: We identified six themes: general impressions (concept and frustration); preferred source of care (institution, specialty, and individual provider); facilitators (VA staff facilitation and proactive Veterans); barriers (complexity, lack of responsiveness, lack of local providers, and poor coordination); perceived sources of VCP problems (learning curve, leadership and staff, and politics); and unintended negative impact (responsibility for costs of care and discontinued access to community care). DISCUSSION: Most Veterans who had received care through the VCP felt that it improved their access to care. However, accessing care through the VCP is a complex process that requires proactive Veterans and active support from the VA, third-party administrators, and availability of participating community providers. Veterans’ abilities to navigate this process and the level of support provided varied widely. Even patients who did receive care through VCP found the process challenging. Greater support is needed for some Veterans to successfully access VCP care because Veterans who need care the most may be the least able to access it.